(untitled) (UTILITY: Jurnal Ilmiah Pendidikan dan Ekonomi, 2018)
Economic growth as a quantitative measure that describes the development of an economy in a given year when compared with the previous year. Economic growth means the development of economic activities that cause goods and services produced in the community to increase and the welfare of society increases. Each region seeks to increase economic growth and stability, one of which is Riau Islands Province. To see how the economic growth of Riau Islands Province, then conducted a study entitled Economic Growth Riau Islands Province. The data source used is secondary data with descriptive data analysis method. From the analysis, it is known that the economic growth of Kepulauan Riau Province in the year of 2016 is 5.03% with the highest growth rate in the big and retail trade, car and motorcycle repairs 9.54%.